Geotechnics for Transportation Infrastructure Recent Developments, Upcoming Technologies and New Concepts, Volume 1 - Sundaram, Ravi; Shahu, Jagdish Telangrao; Havanagi, Vasant (Lecture Notes in Civil Engineering,, 2019)
This book presents selected papers from the International Symposium on Geotechnics for Transportation Infrastructure (ISGTI 2018). The research papers cover geotechnical interventions for the diverse fields of policy formulation, design, implementation, operation and management of the different modes of travel, namely road, air, rail and waterways. This book will be of interest to academic and industry researchers working in transportation geotechnics, as also to practicing engineers, policy makers, and civil agencies.